Energy system contributions during high intensity exercise - Gastin, P. B. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
This research investigated the aerobic and anaerobic energy system contributions during high intensity exercise. An analysis of data in the literature was undertaken along with a re-working of previous data. Standard regression techniques on data taken from studies over the past 15 years (N = 17) has resulted in a number of summary tables and figures. Some recent, previously unpublished data will also be discussed. Much of the information published in scientific texts and the coaching literature on the topic of energy system contribution has its origins back in the 1970s, taken from studies that employed inappropriate methodologies to investigate the problem. The introduction of breath by breath gas analysis and the use of the accumulated oxygen deficit method to proportion energy system contributions have enabled a re-evaluation of traditionally held beliefs.The classical figure that represents the interaction between the energy systems over varying durations of exhaustive exercise depicts a slow responding aerobic system to the demands of exercise such that the contribution of aerobic metabolism to high intensity, short duration exercise has been considered quite insignificant. This is clearly not the case. The crossover to predominantly aerobic energy system supply occurs between 15-30s during simulated 400, 800 and 1500m running events. After only 30s of exercise the oxygen uptake can be as high as 90% of the athlete`s maximum. A 60s exhaustive effort is fuelled by approximately equal contributions from the aerobic and anaerobic system. Textbook data repeatedly suggest it to be 70:30 in favour of the anaerobic system. The time course of the interaction between the energy systems, and in particular the role of the aerobic energy system during high intensity exercise, appear to have been misrepresented over many years. A more complete understanding of the energetics of exercise is essential if training prescription is to be effective.